Candida antarctica lipase-catalyzed synthesis and characterization of novel acrylic teroligomers - Baldessari, Alicia; Fatema, M. Kaniz; Nonami, Hiroshi; Erra Balsells, Rosa; Rustoy, Eduardo Miguel
The synthesis of three novel low molecular weight acrylic terpolymers, containing at random sequences of ethyl acrylate, acrylic acid and N-(2-hydroxyethyl)acrylamide, catalyzed by Candida antarctica lipase was successfully conducted in organic media. For the first time, these products have been enzymatically synthesized using ethyl acrylate as the only monomer starting material and taking advantage of a triple activity displayed by the lipase. In the presence of ethanolamine, the enzyme not only catalyzes the chain polymerization of ethyl acrylate but also the aminolysis and hydrolysis of the pendant ester groups affording the terpolymers. The products were characterized by 1H and 13C NMR and UV-MALDI-TOF-MS. Fil: Baldessari, Alicia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina Fil: Fatema, M. Kaniz. Ehime University; Japón Fil: Nonami, Hiroshi. Ehime University; Japón Fil: Erra Balsells, Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Centro de Investigaciones en Hidratos de Carbono. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Centro de Investigaciones en Hidratos de Carbono; Argentina Fil: Rustoy, Eduardo Miguel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Unidad de Microanálisis y Métodos Físicos en Química Orgánica. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Unidad de Microanálisis y Métodos Físicos en Química Orgánica; Argentina